Analisis Kemampuan Literasi Digital di Madrasah Ibtidaiyah Sultan Agung - Achyati, Shofia Dewi; Hikmatuzahwa, Chaerunisa; Wonoseto, Muhammad Galih (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2024)
The function of technology in the 4.0 era in education is to increase the effectiveness and efficiency of the teaching and learning process as an effort to achieve educational goals, because in the current digital era, information that grows rapidly and is difficult to control requires individuals to not only find and use the information they need, but also filter it, evaluate, and select information. This study aims to analyze the digital literacy abilities of students at the primary school level. Researchers used quantitative descriptive analysis method. Based on the data that has been obtained, 26 students in class V of MIS Sultan Agung have good abilities in their digital literacy level. This shows that Madrasah Ibtidaiyah Sultan Agung Yogyakarta has implemented digital literacy well.